MEMBANGUN SISTEM CODE STROKE PADA DUA RUMAH SAKIT PENDIDIKAN DI INDONESIA - Rakhmad Hidayat,*,** Hirari Fattah Yasfi,*** Dinda Diafiri,*,** Reyhan Eddy Yunus,**,**** Andi Ade W (Neurona Majalah Kedokteran Neuro Sains, 2020)
STROKE SYSTEM IS RAPID RESPOND SYSTEM FOR ISCHEMIC STROKE PATIENTS CARE TO HAVE IMMEDIATE THERAPY IN ORDER TO INCREASE EFFECTIVENESS AND ACHIEVE MAXIMUM OUTCOME CIPTO MANGUNKUSUMO HOSPITAL AND UNIVERSITAS INDONESIA HOSPITAL ARE EDUCATIONAL HOSPITALS WITH DIFFERENT BACKGROUND RESOURCES FACILITIES AND CONDITIONS IN CODE STROKE SYSTEM IMPLEMENTATION